Zhuyu Annao decoction promotes angiogenesis in mice with cerebral hemorrhage by inhibiting the activity of PHD3. (November 2021) - Wu, L; Hu, Y; Jiang, L; Liang, N; Liu, P; Hong, H; Yang, S; Chen, W
Some traditional Chinese decoctions, such as Zhuyu Annao, exert favorable therapeutic effects on acute cerebral hemorrhage, hemorrhagic stroke, and other neurological diseases, but the underlying mechanism remains unclear. This study aimed to determine whether Zhuyu Annao decoction (ZYAND) protects the injured brain by promoting angiogenesis following intracerebral hemorrhage (ICH) and elucidate its specific mechanism. The effect of ZYAND on the nervous system of mice after ICH was explored through behavioral experiments, such as the Morris water maze and Rotarod tests, and its effects on oxidative stress were explored by detecting several oxidative stress markers, including malondialdehyde, nitric oxide, glutathione peroxidase, and superoxide dismutase. Real-time quantitative RT-PCR and WB were used to detect the effects of ZYAND on the levels of prolyl hydroxylase domain 3 (PHD3), hypoxia-inducible factor-1α (HIF-1α), and vascular endothelial growth factor (VEGF) in the brain tissues of mice. The effect of ZYAND on the NF-κB signaling pathway was detected using a luciferase reporter gene. A human umbilical cord vascular endothelial cell angiogenesis experiment was performed to determine whether ZYAND promotes angiogenesis. The Morris water maze test and other behavioral experiments verified that ZYAND improved the neurobehavior of mice after ICH. ZYAND activated the PHD3/HIF-1α signaling pathway, inhibiting the oxidative damage caused by ICH. In angiogenesis experiments, it was found that ZYAND promoted VEGF-induced angiogenesis by upregulating the expression of HIF-1α, and NF-κB signaling regulated the expression of HIF-1α by inhibiting PHD3. ZYAND exerts a reparative effect on brain tissue damaged after ICH through the NF-κB/ PHD3/HIF-1α/VEGF signaling axis.